El rol de los títulos emitidos por el Banco Central en los últimos 20 a\~nos de política monetaria argentina - Esteban Rodríguez; Jorge E. Carrera; Gaspar Maciel (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2023)
– This paper focuses on the implementation of the BCRA's monetary policy from the end of the convertibility regime to the present. The issuance of interest-bearing liabilities was a central element that gave the BCRA operational autonomy to implement its monetary policy within diverse macroeconomic contexts. To review this history, which leaves many lessons for the present and near future, we made a three-level analysis. In the first section, we describe a stylized analysis of the balance sheets effects of different monetary sterilization operations. In the second section, we collect the different regulatory changes that were introduced on the securities issued by the BCRA. Finally, in the third section, we review the recent history of the monetary policy and the economic context in which the BCRA issued securities.
Keywords: E52; E58; 330; Monetary Policy; Central Bank; Interest-bearing liabilities